The intimacy of power: gender and US naval visits to Haifa port 1979–2001. Issue 1 (2nd January 2019) - Aharoni, Sarai B.
Abstract : Using a method of feminist historical ethnography, this article offers a microanalysis of US Sixth Fleet port calls, Rest and Recreation, and naval diplomacy in Haifa port over the period 1979–2001. The documentation of everyday civil–military encounters in the city supports the claim that in the Mediterranean context, American military expansion was welcomed both by political elites and by the general public. In this process, a politics of consensus was built through repeated activities, ceremonies and cultural frames, which stressed the shared values and importance of US–Israel relations. Although the negative effects of routine visits (vandalism, crime, prostitution and rape) were never publicly acknowledged on the national level, two mechanisms for containing and minimizing urban conflict were developed over time by local officials and entrepreneurs. First, a discursive framing of port calls as a form of militarized tourism enabled municipal authorities to carefully plan and control the daily routine of foreign servicemen, including their exchanges with local residents. Second, the urban decay of the Haifa port district enabled the creation of intimate and confined bars that catered for American soldiers far from residential areas. Narratives of and about women who were involved as agents in the daily maintenance of these spaces reveal that intimacy, sexuality and even motherly love were significant for the development of both mechanisms. Furthermore, local forms of militarized femininity, namely the care for male soldiers as a motherly duty and the trivialization of sexual violence, were expanded to include US servicemen, contributing to the normalization of foreign military presence.